Atomic structures of ordered monolayer GP zones in Mg-Zn-X (X= Ca, Nd) systems. (15th July 2022) - Cheng, Du; Hoglund, Eric R.; Wang, Kang; Howe, James M.; Agnew, Sean R.; Zhou, Bi-Cheng
Abstract: Atomic structures of ordered monolayer Guinier-Preston (GP) zones in Mg-Zn-X (X = Ca, Nd) systems are predicted based on first-principles calculations combined with the statistical-mechanical approach of cluster expansion. Multiple metastable GP zones with various compositions are identified in both systems. The predicted metastable structures in both systems show striking similarities and are all structurally related to monolayer Mg2 X with each X atom 6-fold coordinated by Mg atoms on the HCP basal plane. An increased number of Mg atoms in monolayer Mg2 X are replaced by Zn atoms to form ordered GP zones at an increased Zn/X ratio due to strong attractive interactions between Zn and X solutes, which ultimately leads to lower formation energies of the GP zones. Simulated TEM images and diffraction patterns of the predicted structures agree well with prior experimental observations. Graphical abstract: Image, graphical abstract